Contributions of carbonaceous particles from fossil emissions and biomass burning to PM10 in the Ruhr area, Germany. (September 2018) - Küpper, Miriam; Quass, Ulrich; John, Astrid C.; Kaminski, Heinz; Leinert, Stephan; Breuer, Ludger; Gladtke, Dieter; Weber, Stephan; Kuhlbusch, Thomas A.J.
Abstract: Recently, rising concentrations of PM emitted by biomass burning for residential heating purposes have been observed at sites throughout Europe. They are contributing to exceedances of the PM10 daily limit value and have been shown at some sites to even outrun PM reductions achieved by mitigation strategies focussing on traffic emissions. To assess the contribution of fossil and biogenic carbonaceous matter to PM10 mass we measured equivalent black carbon (eBC) by 7-wavelength Aethalometer, elemental and organic carbon (EC/OC) via thermo-optical analysis and levoglucosan by ion chromatography at two monitoring sites (one urban background and one traffic site) in the Ruhr area, Germany, over a period of 16 months (September 2013–December 2014). To achieve differentiation between concentrations of carbonaceous particulate matter (CM) emitted by fossil fuel combustion (CMfossil ) and CM concentrations attributed to biomass burning (CMbiomass ) the so-called "Aethalometer approach" (Sandradewi et al., 2008) mainly based on eBC measurements was applied. Another approach based on levoglucosan as a mono-tracer for biomass burning emissions was used for evaluation of the Aethalometer approach resulting in well correlated concentrations for both approaches within the heating period (r 2 of 0.78 and 0.84, slope of 0.70 and 0.82 for urban background and traffic site, respectively). This confirms the general applicability of both methods. However, sensitivity studies regarding differing fixed factors applied in both approaches for converting eBC or levoglucosan to CM, respectively, showed that slight variation in pre-defined constants could result in CM bias by up to approximately 50%. As a consequence well-considered choice of these conversion factors is considered as crucial to warrant credibility of different CM values. Concentrations of CMfossil were found to be almost constant during the whole period whereas biomass emissions exhibited significant seasonal variability, leading to heating period/summer ratios of 2.82 and 2.51 at the urban background and traffic site, respectively. During the heating period concentrations of CMbiomass summed up to 2.8 μg/m 3 (14.6% of PM10 ) at the urban background site compared to 2.2 μg/m 3 (11.2% of PM10 ) at the traffic site - being in good agreement with those determined for other European sites. The PM10 share of CMbiomass was almost equal to CMfossil at the traffic site whilst at the urban background site contributions of fossil fuel emissions were even outrun during the colder months. Additionally, data from those two sites observed during the study indicate that emissions from biomass burning processes might be of similar relevance as fossil fuel emissions in terms of exceedances of the daily PM10 limit value. Highlights: Significant winter contribution of biomass burning at both sites. Biomass burning PM10 exceeds fossil contributions in wintertime at background site. Good agreement between approaches quantifying biomass burning contributions to PM10 .